AKULTURASI KEBUDAYAAN CINA DAN EROPA DENGAN KEBUDAYAAN PALEMBANG PADA ARSITEKTUR MASJID AGUNG PALEMBANG - Sari, Dewi Purnama; Setyawati, Dewi; Ramadhan, Nur (Universitas Muhammadiyah Palembang, 2025)
The geographical location of Palembang, which is one of the trading ports, has caused many foreign nations to come to this city, including Chinese and Europeans. Direct interaction between the people of Palembang and Chinese and European cultures brought by traders who came to Palembang caused acculturation in various things, including in terms of architectural art. One of the buildings whose architecture is influenced by Chinese and European cultures is the Great Mosque of Palembang. The influence of Chinese architecture on the Great Mosque of Palembang can be seen on the roof, ceiling, old tower, and the use of typical Chinese colors on several building ornaments. Meanwhile, the influence of European architecture can be seen on the white pillars in the Doric shape on the terrace and the hall of the mosque, in addition, the influence of European architecture can also be seen in the use of stained glass ornaments in several parts of the Great Mosque of Palembang. Meanwhile, the typical Palembang architectural style found in the Great Mosque of Palembang can be seen in the carving art found on several ornaments in the Great Mosque of Palembang.